RADIATION THERAPY COMMUNICATION—REIRRADIATION OF A NASAL TUMOR IN A BRACHYCEPHALIC DOG USING INTENSITY MODULATED RADIATION THERAPY. Issue 5 (5th January 2016) - Rancilio, Nicholas J.; Custead, Michelle R.; Poulson, Jean M.
Abstract : A 5‐year‐old spayed female Shih Tzu was referred for evaluation of a nasal transitional carcinoma. A total lifetime dose of 117 Gy was delivered to the intranasal mass in three courses over nearly 2 years using fractionated intensity modulated radiation therapy (IMRT) to spare normal tissues. Clinically significant late normal tissue side effects were limited to bilaterally diminished tear production. The patient died of metastatic disease progression 694 days after completion of radiation therapy course 1. This case demonstrates that retreatment with radiation therapy to high lifetime doses for recurrent local disease may be well tolerated with IMRT.